THE INFLUENCE OF MANAGEMENT EFFECTIVENESS, TRANSFORMATIONAL LEADERSHIP, PLACEMENT AND TEAM WORK ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR CIVIL STATE EMPLOYEES IN THE DEPARTMENT OF EDUCATION ACEH PROVINCE - Suryadi Jaya; Henry Eryanto; Suparno Eko Widodo (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research aims to analyze the influence of management effectiveness, transformational leadership, placement, and team work towards organizational citizenship behavior of Civil Servants at The Department of Education Aceh Province. Which method used in this research is a survey method. The population in this study were all civil servants amounting to 283 people. While the sample is all class III civil servants from all fields in the Department of Education Aceh Province amounting to 100 people. The data collection method is done by interview, questionnaire, and study documentation. The data analysis used in this research is analysis Multiple regression processed using SPSS and PLS programs Smart 3.0. The results showed that the effectiveness of management, and transformational leadership, does not have a significant direct effect on organizational citizenship behavior. Placement, and teamwork matter directly significant on organizational citizenship behavior. Effectiveness management and placement have a significant direct effect on teamwork. Transformational leadership does not have a significant direct effect on teamwork. Management effectiveness, and transformational leadership not has a significant direct effect on the placement. Transformational leadership is influential directly positive on management effectiveness